IMMUNO-INFLAMMATORY MARKERS ASSOCIATED WITH LEFT VENTRICULAR REMODELING IN ISCHEMIC HEART DISEASE (Modern American Journal of Medical and Health Sciences, 2025)
The article explores endothelial damage factors in arterial hypertension and ischemic heart disease, forming a cardiovascular syntropy. The cytokines considered as markers of endothelial dysfunction include IGF-I, VEGF, TGF-β1, and serum procalcitonin. The study found that patients with elevated VEGF levels have a high risk of developing and progressing cardiovascular pathology—particularly myocardial fibrosis and hypertrophy—against the background of arterial hypertension, regardless of its severity.